Nested core collections maximizing genetic diversity in Arabidopsis thaliana - Heather I. McKhann; Christine Camilleri; Aurélie Bérard; Thomas Bataillon; Jacques David; Xavier Reboud; Valérie Le Corre; Christophe Caloustian; Marta Gut; Dominique Brunel (2004)
Summary The successful exploitation of natural genetic diversity requires a basic knowledge of the extent of the variation present in a species. To study natural variation in Arabidopsis thaliana , we defined nested core collections maximizing the diversity present among a worldwide set of 265 accessions. The core collections were generated based on DNA sequence data from a limited number of fragments evenly distributed in the genome and were shown to successfully capture the molecular diversity in other loci as well as the morphological diversity. The core collections are available to the scientific community and thus provide an important resource for the study of genetic variation and its functional consequences in Arabidopsis . Moreover, this strategy can be used in other species to provide a rational framework for undertaking diversity surveys, including single nucleotide polymorphism (SNP) discovery and phenotyping, allowing the utilization of genetic variation for the study of complex traits.